2001
DOI: 10.1046/j.1445-5994.2001.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of febrile neutropenia in the Royal Darwin Hospital, 1994–99

Abstract: Gram-positive organisms are the predominant pathogens in febrile neutropenic episodes at the RDH. Standard empirical therapy with an extended-spectrum penicillin and an aminoglycoside remains appropriate, with the addition of vancomycin when clinical status fails to improve. When practising in the Top End, particular consideration should be given to skin integrity and scabies and testing for Strongyloides in Aboriginal patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
(21 reference statements)
2
11
0
Order By: Relevance
“…One study from Malaysia reported that 66% of FN in their cancer patients receiving chemotherapy was due to GN organisms. [1,4,5,6,7] The finding from this audit is similar to those in other developed countries including one from Darwin in Australia, [8] where most of the isolated organisms are gram positive cocci. And majority of these are coagulase negative staphylococci.…”
Section: Discussionsupporting
confidence: 71%
“…One study from Malaysia reported that 66% of FN in their cancer patients receiving chemotherapy was due to GN organisms. [1,4,5,6,7] The finding from this audit is similar to those in other developed countries including one from Darwin in Australia, [8] where most of the isolated organisms are gram positive cocci. And majority of these are coagulase negative staphylococci.…”
Section: Discussionsupporting
confidence: 71%
“…Similar defects in neutrophil function have also been observed with other co-morbidities, such as increased alcohol consumption, renal failure and thalassemia [6], [50][52]. Increased incidence of melioidosis is also noted in neutropenic patients [53], [54], as well as patients with chronic granulomatous disease [55], [56]. Interestingly, the neutrophil-differentiating cytokine granulocyte colony-stimulating factor (G-CSF) has been used as a treatment for melioidosis, with mixed results; it is reported to reduce mortality of melioidosis patients in Australia [57], but is only associated with prolonged survival in Thailand patients [58].…”
Section: Introductionsupporting
confidence: 56%
“…A recent study conversely indicated that neutrophil recruitment during melioidosis may be detrimental in controlling bacterial numbers and host survival, and suggested monocytes may be important to limit B. pseudomallei infection [71]. There is indirect evidence that neutrophils may play a role in controlling melioidosis infection through correlative findings based on cellular recruitment to the infection site, predisposing conditions, and adjunctive therapies; however any protective properties have not been clearly confirmed to be attributable to neutrophils [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54]. Notably, in vitro studies to delineate the relative abilities of neutrophils to kill B. pseudomallei have provided conflicting results [45], [55], [56], [57].…”
Section: Discussionmentioning
confidence: 99%
“…mice lacking NADPH oxidase, an important enzyme in the generation of the microbicidal respiratory burst primarily utilized by neutrophils, are more susceptible to B. pseudomallei infection [43], iv. diabetes mellitus, which is the primary predisposing condition for melioidosis, is associated with impaired neutrophil function [44], [45], [46], [47], v. neutropenic individuals are more susceptible to B. pseudomallei infection and development of fatal disease [48], [49] and, vi. granulocyte colony-stimulating factor (G-CSF), which stimulates neutrophil differentiation, prolongs the survival of melioidosis patients, though a direct link to enhanced neutrophil function has not been proven [50], [51], [52], [53], [54].…”
Section: Introductionmentioning
confidence: 99%